UNESCO Global Geoparks and Geomorphology: A Bibliometric Analysis of Global and Brazilian Scientific Production - Wilhelm, Martiele; Vieira Romano, Fabiane; Weiss, Raquel; Guilherme Aita Pippi, Luis (Revista Brasileira de Geomorfologia, 2025)
UNESCO Global Geoparks play a strategic role in the conservation of geological heritage, the promotion of geoscience education, and sustainable territorial development. This article presents a bibliometric analysis of international and Brazilian scientific production on geoparks, with a focus on the presence of geomorphology between 2007 and 2024. A total of 172 articles from Scopus and Web of Science databases were analyzed, revealing exponential growth in publications, particularly in countries such as China, Portugal, Spain, and Italy. In Brazil, scientific output remains recent and thematically narrow, concentrated in a few geoparks. The thematic analysis revealed that, although geomorphology is crucial for understanding and interpreting landscapes, its application remains limited and unsystematic, particularly in national studies. This gap underscores the need to integrate geomorphological knowledge more effectively into geopark management, conservation, and territorial planning strategies. The study reinforces the importance of technical training, research networks, and the inclusion of geomorphology as an analytical tool for geoconservation and landscape interpretation.